The emergence of Indian multinationals: An empirical study of motives, status-quo and trends of Indian investments in Germany - Rajnish Tiwari; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2009)
Germany has advanced to the position of a key destination for Indian multinational enterprises in their spirited pursuit of growth opportunities overseas. In 2008, Indian firms invested an estimated amount of US 1.8 billion in Germany while 16 acquisitions by Indian firms were monitored, up from 7 in 2007. In fact, Indian FDI stock in Germany seems to have surpassed German FDI stock in India. Our research shows that, as of October 2008, 123 Indian MNEs with 167 subsidiaries were active in Germany and had approx. 20,000 full-time employees on their pay-rolls. However, there has been hardly any independent, academic research, so far, on Indian investments in Germany, especially on the motives, experiences, and employment effects on the host and home economies. The present study, presumably the only empirical study of Indian firms overseas to date, provides unique insights into the motives, operations, experiences, and future plans of Indian firms. It shows that Indian firms have generally performed well and intend to further strengthen their operations, including in research & development activities, in Germany. Nonetheless, firms are also faced with several challenges, including but certainly not limited to cross-cultural issues, which need to be mastered. There are also sectoral differences in the motives, experiences, and location selection criteria of Indian MNEs.
urn:nbn:de:gbv:830-tubdok-5549
Keywords: 650; Globalization; Multinational Enterprises; Foreign Direct Investments; Mergers & Acquisitions; India